Edukasi Pencegahan Insomnia pada Remaja di SMK Baiturrahim Jambi - Nurfitriani Nurfitriani (3031-8572, 2022)
Insomnia is a sleep disorder that occurs at night, which generally causes poor quality sleep or has a short sleep time. School students with various activities such as doing homework, watching television, playing games, or other social media often take up their rest time so that it can interfere with their rest time and gradually insomnia symptoms can occur. The purpose of this devotion is to explain the importance of sleep for adolescents and prevent the occurrence of insomnia in adolescents. The target of service is aimed at the students of SMK Baiturrahim Jambi totaling 22 people. The method of implementing activities by conducting education about insomnia using leaflets and PPT, and demonstrations of relaxation (deep breath) was carried out in March - August 2021. The result of this service is the implementation of the real work lectures of D3 nursing students and the implementation of the service runs smoothly even though currently the conditions are pandemic, but can be carried out face-to-face while still implementing health protocols. The vast majority (75%) of students actively ask questions and discussions around insomnia. Students can repeat the material presented and are also able to re-demonstrate one of the ways to prevent insomnia with relaxation techniques (deep breath).